(untitled) (East West Medical College Journal, 2025)
Uterine scar dehiscence is the opening of the uterine incision. It is potentially a life threatening complication. Though it is a rare complication of caesarean section but now-a-days it is increasing as caesarean delivery is also increasing. It is more common following vaginal birth after caesarean (VBAC). It leads to postpartum hemorrhage, pelvic hematoma, pelvic abscess, endomyometritis, generalized and localized peritonitis and sepsis. Here we report a case of a 25 year old female who presents with abdominal distention with pyrexia following VBAC. Investigation revealed incomplete uterine scar rupture and huge ascites with left sided mild pleural effusion. The case was managed by laparotomy and drainage of about 6L of encysted pus. EWMCJ Vol. 13, No. 2, July 2025: 149-151